Towed array geometry estimation during ship's moneuvering - Jesus, S. M. (2014)
Towed arrays of hydrophones are commonly used as receiver apparatus for determining the directionality of the underwater acoustic field. It is well known that a line array beam response has a inherent left-right ambiguity and that any deformation of the array will produce a distortion on the estimated acoustic field directionality.